Can teachers know learners' minds? Teacher empathy and learner body language in English language teaching - McAlinden, Maggie (Springer, 2014)
Empathy has often been associated with how people come to know the minds of others. Theory of mind (ToM) proposes that through social cognition people make unique inferences about unobservable mental states such as intentions, goals and beliefs. This chapter explores the association between teacher empathy, ToM and interculturality, and the expression and interpretation of emotion in intercultural educational settings. The chapter raises questions about the universality of non-verbal emotional expression and interpretation of emotion across cultures, and suggests that teachers may not always be accurate in their interpretations of learners' emotional cues in intercultural encounters. The chapter concludes that reflexivity and empathy are essential elements of being in interculturally effective educator.